Integrasi Data Kapal untuk Penerbitan Dokumen RPK dan Penambahan Pelabuhan Singgah pada Sistem Simlala oleh PT. Citra Maritime Batam - Agnes Soraya Br Sinuraya; Yursal Yursal; Dina Rispianti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to analyze the process of issuing the Ship Operation Plan RPK document and the procedure for adding a port of call, both managed by PT. Citra Maritime Batam using the Sea Traffic and Transport Information System SIMLALA. Within the national sea transport ecosystem, the RPK document serves as the official approval that allows Indonesian-flagged vessels to operate, covering both fixed-route liner and non-fixed-route tramper voyages. The research methodology employed is a combination of Field Research and Library Research. Data were collected through direct observation in the field to understand the detailed steps within the SIMLALA system, alongside literature review to obtain the theoretical foundation related to the RPK document and maritime administration mechanisms. The findings of this study highlight that the main objective of this process is to ensure that the ship can sail in compliance with applicable regulations, possessing valid certificates and approved routes. PT. Citra Maritime Batam, acting as the agent, plays a vital role in integrating ship data to complete the necessary documentation at Batam Port. The key to the smooth running of this process is effective coordination between the agent and relevant authorities in Batam to guarantee the seamless arrival, departure, and adherence to government regulations, thereby ensuring ship operational processes run without systemic or field-level obstacles.